PENINGKATAN PRESTASI BELAJAR BAHASA INDONESIA DALAM MENULIS PUISI PADA SISWA MELALUI IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TGT - Sukiasih, Made (Jurnal Imiah Pendidikan dan Pembelajaran, 2018)
This research was carried out in Class IX-A of Singaraja State Middle School 2 in the even semester of the 2017/2018 school year, with the condition that the average learning achievement was only 63.37, this condition was very low and did not meet the minimal expected score. The percentage of achievement has only reached 50.00%. The purpose of writing this class action research was to improve the learning achievement of Indonesian Language through the implementation of the TGT cooperative learning model. The data was collected assessment of poetry written by students, then analyzed using quantitative descriptive methods. Data was presented in the form of average learning achievement and completeness learning process. The results obtained from this study were the development of very positive learning achievements. At first the average student achievement was only; 63,37 with learning completeness only; 50.00%, then after the implementation of Cycle I it increased to an average; 76.42 with learning completeness reaching 72.97%. From cycle I to cycle II there was also an increase which reached an average of 83.26 and learning completeness was 91.89%. The conclusion obtained from this study is that the implementation of the TGT cooperative learning model can improve Indonesian learning achievement in writing poetry for students of class IX-A in the even semester of the academic year 2017/2018. Keywords: TGT cooperative learning model, learning achievement in writing poetry